Entrepreneurial Intention of Young Generation in Metropolis - Santirianingrum Soebandhi; Sugito Muzaki; Agus Sukoco (IJEBD (International Journal of Entrepreneurship and Business Development), 2018)
Purpose: This study is aimed to analyze entrepreneurial intention of youth during the process towards young entrepreneur that is intellectually, mentally, and economically independent, approached by planned behavior principles. Design/methodology/approach: The quantitative research method with three variables (attitude, social norm and behavior) was used as the predictor of young entrepreneurial intention. The respondents are 127 young adult aged 18-28 years old with High School/Vocational School as their minimum education and domiciled in Surabaya and Sidoarjo. Likert scale with 5 levels was used as the research questionnaire, distributed with two methods that are filling out the questionnaire by online and manually. Findings: The result shows that attitude, social norm and behavior variable give positive contribution in creating young generation entrepreneurial intention in metropolis. Indicator which gives strong contribution in triggering entrepreneurial intention of young generator is that the paradigm of being entrepreneur is able to give benefits, satisfaction and as a choice. Social factor encouraging establishing the businesses are friends and relatives. Behaviors impelling it are the feeling of being able and having enough knowledge in starting the business as well as able to manage the business. The constraints are coming from little encouragement of family and low belief for getting success. Research limitations/implications: This study was conducted in two urban areas in East Java. Further research can be done on a wider area. Practical implications: Entrepreneurial intention of youth is unique inasmuch as it has environment and complexity characteristics which enables to give impact towards society. Originality/value: This study focuses on urban areas with young adults respondents which can provide new references to factors that may encourage or hamper their interest in becoming entrepreneurs Paper type: Research paper